Gender-Based Violence And Ethical Relativism: A Shadow Pandemic Ravaging Nigeria - Sotonye Big-Alabo (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2022)
Gender-Based Violence (GBV) is a disturbing phenomenon prevalent in all regions of the world. GBV is seen as any harmful act that is carried out against a person’s consent and that is as a result of socially ascribed (gender) dissimilarities between males and females. The study exposes that the fight against GBV has been unsuccessful because of several factors which include the acceptance of such actions by some traditions and cultures, therefore, bringing to the fore conventional ethical relativism, in other words, cultural relativism. The study concluded that the rate of GBV in Nigeria is soaring high and the neglect to tackle it has made it turn out to be a shadow pandemic ravaging Nigeria. Consequently, the study amongst others recommends that the Nigerian National Assembly should enact new laws against GBV because its eradication can only be possible using the law as an instrument of social change.